2013
DOI: 10.1099/vir.0.054379-0
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked glycosylation is essential for the yellow head virus replication cycle

Abstract: Yellow head virus (YHV) particles contain a nucleocapsid protein (p20) and two envelope glycoproteins (gp116 and gp64). The glycans attached to the two glycoproteins are N-linked and are complex and high mannose types, respectively. Here, we show that treatment with the N-linked glycosylation inhibitor tunicamycin in YHV-infected black tiger shrimp (Penaeus monodon) resulted in less severe yellow head disease and reduced mortality when compared with untreated control shrimp. Quantitative real-time reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Of the potential N-linked glycosylation sites in gp116 and gp64, six in gp116 and three in gp64 have been identified to possess mannose-rich glycans, with those in gp116 also possessing N-acetylgalactosamine and N-acetylglucosamine terminal-type sugars (Soowannayan et al, 2011). Injection of shrimp with tunicamycin to inhibit N-linked glycosylation prior to YHV challenge results in reduced viral RNA and protein levels in hemolymph, numbers of mature virions in cells and mortality rate, confirming that the gp116 and gp64 glycosylation process is critical to YHV replication and thus disease (Soowannayan et al, 2013). In variants of YHV1 (YHV1b) as well as a potential recombinant virus derived from ancestral YHV1b and YHV5 genotypes, a 54 amino acid deletion occurs at the N-terminus of gp116 just downstream of the pp3 TM3 cleavage site, but this deletion appears to have little if any impact on the pathogenic potential of these variants relative to YHV1a Gangnonngiw et al, 2009;Senapin et al, 2010).…”
Section: Genome Organization Rna Transcription and Viral Proteinsmentioning
confidence: 87%
“…Of the potential N-linked glycosylation sites in gp116 and gp64, six in gp116 and three in gp64 have been identified to possess mannose-rich glycans, with those in gp116 also possessing N-acetylgalactosamine and N-acetylglucosamine terminal-type sugars (Soowannayan et al, 2011). Injection of shrimp with tunicamycin to inhibit N-linked glycosylation prior to YHV challenge results in reduced viral RNA and protein levels in hemolymph, numbers of mature virions in cells and mortality rate, confirming that the gp116 and gp64 glycosylation process is critical to YHV replication and thus disease (Soowannayan et al, 2013). In variants of YHV1 (YHV1b) as well as a potential recombinant virus derived from ancestral YHV1b and YHV5 genotypes, a 54 amino acid deletion occurs at the N-terminus of gp116 just downstream of the pp3 TM3 cleavage site, but this deletion appears to have little if any impact on the pathogenic potential of these variants relative to YHV1a Gangnonngiw et al, 2009;Senapin et al, 2010).…”
Section: Genome Organization Rna Transcription and Viral Proteinsmentioning
confidence: 87%
“…For example, in PCEs where a temperature range is reported, the impacts of temperature fluctuation can be considered with respect to the outcomes of the study, especially of those that report temperature ranges across a large gradient ($4-6 C variation). 27,[187][188][189][190][191][192] Shrimp acclimation period was reported for more than half of the studies analysed (66%, 122/186 for multiple viruses in non-purified viral inoculums or un-processed inoculum types was very rarely reported (4%, 8/186).…”
Section: Reported Information In Shrimp Pcesmentioning
confidence: 99%
“…Studies should aim to report a range or mean ± SD for water quality parameters, as it provides information as to the consistency of the conditions maintained throughout the experiment. For example, in PCEs where a temperature range is reported, the impacts of temperature fluctuation can be considered with respect to the outcomes of the study, especially of those that report temperature ranges across a large gradient (~4–6°C variation) 27,187–192 . Shrimp acclimation period was reported for more than half of the studies analysed (66%, 122/186).…”
Section: Reported Information In Shrimp Pcesmentioning
confidence: 99%
“…In M. japonicus , the phosphorylation of focal adhesion kinase (FAK) promotes the activation of multiple immune signaling pathways, including antiviral response during white spot syndrome virus (WSSV) infection ( 22 ). The envelope proteins, gp116 and gp64, of yellow head virus (YHV), possess N-linked glycosylation ( 23 ), which accelerates the formation and release of YHV virions into the hemolymph of infected shrimp ( Penaeus monodon ), hence increasing the severity of the disease ( 24 ). Similarly, we previously revealed that the glycosylation of Penaeus vannamei hemocyanin increases its antibacterial and agglutination activity against Vibrio alginolyticus and Vibrio fluvialis ( 25 ).…”
Section: Introductionmentioning
confidence: 99%